Profit over people : neoliberalilsm and global order - Chomsky, Noam (Madhyam Books, 1999)
In Profit Over People, Noam Chomsky takes on neoliberalism: the pro-corporate system of economic and political policies presently waging a form of class war worldwide. By examining the contradictions between the democratic and market principles proclaimed by those in power and those actually practiced, Chomsky critiques the tyranny of the few that restricts the public arena and enacts policies that vastly increase private wealth, often with complete disregard for social and ecological consequences.